2006
DOI: 10.1007/s00125-006-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of intestinal lipoprotein containing apolipoprotein B-48 in Psammomys obesus: impact of dietary n-3 fatty acids

Abstract: Aims/hypothesis Emerging evidence underscores the important role of the small intestine in the pathogenesis of dyslipidaemia in insulin resistance and type 2 diabetes. We therefore tested the hypothesis that n-3 fatty acids improve the various events governing intra-enterocyte lipid transport in Psammomys obesus gerbils, a model of nutritionally induced metabolic syndrome. Materials and methods Experiments were carried out on Psammomys obesus gerbils that were assigned to an isocaloric control diet and a diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 58 publications
(57 reference statements)
5
23
0
1
Order By: Relevance
“…Recent fi ndings from animal models of IR are consistent with data from humans that have revealed the overproduction of intestinal apoB-48-containing lipoproteins ( 10,11 ). Studies have also consistently supported the concept that inducing IR in various animal models is associated with signifi cant upregulation of the expression of key intestinal genes involved in lipid and lipoprotein metabolism ( 12,13 ).…”
Section: Quantifi Cation and Isolation Of Apob-48 And Apob-100supporting
confidence: 70%
“…Recent fi ndings from animal models of IR are consistent with data from humans that have revealed the overproduction of intestinal apoB-48-containing lipoproteins ( 10,11 ). Studies have also consistently supported the concept that inducing IR in various animal models is associated with signifi cant upregulation of the expression of key intestinal genes involved in lipid and lipoprotein metabolism ( 12,13 ).…”
Section: Quantifi Cation and Isolation Of Apob-48 And Apob-100supporting
confidence: 70%
“…Furthermore, our observations pointed to an undoubtedly important role of the liver in the pathogenesis of metabolic disorders in the progression of nutritionally induced 'diabesity' in P. obesus since the development of these conditions triggered the whole intra-hepatocyte machinery, leading to lipoprotein assembly and favouring the oversecretion of apolipoprotein B-100-lipoproteins [23]. Beneficial effects of diets enriched with n-3 FA were noted on body weight, hyperglycaemia, hyperinsulinaemia and hyperlipidaemia, as well as on intestinal lipogenesis, lipid esterification and de novo apo B-48 synthesis [24,25]. Favourable n-3 FAs clearly impact on the overproduction of intestinal TAG (triacylglycerol)-rich lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…There was a negative correlation between both ABCG5 and G8 and chylomicron cholesterol [83]. In the Psamonas Obesus Levy et al [73,74] showed a reduction in ABC G5/G8 in the intestine. In the intestine of human subjects with type 2 diabetes, ABCG5 and G8 mRNA were both significantly lower compared to controls [71].…”
Section: The Chylomicron In Diabetesmentioning
confidence: 96%
“…In the Sammomas Obesus model of type 2 diabetes, the animals exhibiting weight gain, hyperinsulinaemia and hypercholesterolaemia, NPC1-L1 protein and gene expression were both significantly reduced in the intestine and the authors found a lower capacity to absorb cholesterol compared to controls [73,]. This may suggest interspecies variation but it is a surprising finding considering that this animal model of diabetes has been shown to have increased production of intestinal lipoprotein-containing apo B48 [74]. The mechanism whereby the body is almost completely unable to absorb plant sterols was a mystery until recently.…”
Section: The Chylomicron In Diabetesmentioning
confidence: 99%